RESEARCH ON THE MILLENNIAL GENERATION’S BEHAVIOR TOWARD HALAL CONSUMPTION - Saputro, Edy Purwo; Seyaningrum, Dewi Probowati (JURNAL MANAJEMEN MAKER STIE SULTAN AGUNG, 2023)
Research on the consumption behavior toward halal products is interesting to study, not only because most of the population in Indonesia is Muslim but also because several previous studies’ findings have mixed results, creating a loophole for finding research gaps. This research, therefore, aims to examine several factors influencing the purchase intention of halal products. The sample involved 100 millennial youth represented by the Faculty of Economics and Business (FEB) students, Universitas Muhammadiyah Surakarta (UMS). The test results demonstrated that the three variables impacted purchase intention, i.e., halal awareness, halal logo, and attitude. These results become opportunities and challenges for producers and marketers to spur the role of these three variables to impact the intention to purchase halal products positively. In addition, limitations and suggestions for further research are presented to support theoretical deepening and understanding of the development of research models.